The ninth vibration and other stories - Beck, L. Adams (Lily Adams), 1862-1931 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Ninth Vibration and Other Stories" by L. Adams Beck is a collection of narratives likely crafted during the early 20th century. The stories delve into mystical and spiritual themes, supported by an enchanting backdrop of India and its sublime landscapes. The main narrative of "The Ninth Vibration" follows an introspective character, Ormond, as he embarks on a journey through the Himalayas, encountering otherworldly revelations and profound connections with nature and the divine. The opening of "The Ninth Vibration" introduces us to Ormond as he traverses the picturesque and perilous route from Simla to Tibetan territories. He is eager to discover the elusive "House in the Woods," which belongs to Rup Singh, a pandit who is deeply connected to the legends of the region. Through his discussions with his friend Olesen and his initial climb through dense forests, Ormond learns of the mysterious past surrounding the House and the tragic history of the Maharao, furthering his desire to experience the beauty and spirituality of the Himalayas. As he makes his way, he encounters a sense of danger and the unknown, compounded by the eerie expectation of a chance meeting with a mysterious veiled woman, hinting at deeper issues of love, loss, and enlightenment that will unfold throughout the story. (This is an automatically generated summary.)
The ninth vibration -- The interpreter: a romance of the east -- The incomparable lady: a story of China with a moral -- The hatred of the queen: a story of Burma -- Fire of beauty -- The building of the Taj Mahal -- "How great is the glory of Kwannon!": a Japanese story -- The round-faced beauty: a story of the Chinese court.
Release date is 1999-08-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Short stories; Fantasy fiction; Paranormal fiction